THE PARTICIPATION OF LANDOWNERS IN ORDER TO PROCURE LAND FOR CONSTRUCTION IN THE PROVINCE OF NORTH MALUKU - Baro, Rachmad (Journal of Humanity, 2017)
The provision of land for development needs, often constrained by uncertainty on the ground, the result is still a low percentage of registered land persil, which he believed was still conditioned by the sign/natural land boundary by society, so they are not motivated to certivicate soils, and the implications of its preliminary is the poor quality of the participation of